Intrathymic injection of hematopoietic progenitor cells establishes functional T cell development in a mouse model of severe combined immunodeficiency - Andrea Z. Tuckett; Raymond H. Thornton; Richard J. O’Reilly; Marcel R. M. van den Brink; Johannes L. Zakrzewski (Journal of Hematology & Oncology, 2017)
Abstract Background Even though hematopoietic stem cell transplantation can be curative in patients with severe combined immunodeficiency, there is a need for additional strategies boosting T cell immunity in individuals suffering from genetic disorders of lymphoid development. Here we show that image-guided intrathymic injection of hematopoietic stem and progenitor cells in NOD-scid IL2rγnull mice is feasible and facilitates the generation of functional T cells conferring protective immunity. Methods Hematopoietic stem and progenitor cells were isolated from the bone marrow of healthy C57BL/6 mice (wild-type, Luciferase+, CD45.1+) and injected intravenously or intrathymically into both male and female, young or aged NOD-scid IL2rγnull recipients. The in vivo fate of injected cells was analyzed by bioluminescence imaging and flow cytometry of thymus- and spleen-derived T cell populations. In addition to T cell reconstitution, we evaluated mice for evidence of immune dysregulation based on diabetes development and graft-versus-host disease. T cell immunity following intrathymic injection of hematopoietic stem and progenitor cells in NOD-scid IL2rγnull mice was assessed in a B cell lymphoma model. Results Despite the small size of the thymic remnant in NOD-scid IL2rγnull mice, we were able to accomplish precise intrathymic delivery of hematopoietic stem and progenitor cells by ultrasound-guided injection. Thymic reconstitution following intrathymic injection of healthy allogeneic hematopoietic cells was most effective in young male recipients, indicating that even in the setting of severe immunodeficiency, sex and age are important variables for thymic function. Allogeneic T cells generated in intrathymically injected NOD-scid IL2rγnull mice displayed anti-lymphoma activity in vivo, but we found no evidence for severe auto/alloreactivity in T cell-producing NOD-scid IL2rγnull mice, suggesting that immune dysregulation is not a major concern. Conclusions Our findings suggest that intrathymic injection of donor hematopoietic stem and progenitor cells is a safe and effective strategy to establish protective T cell immunity in a mouse model of severe combined immunodeficiency.